Composite cement foam board and preparation method thereof

By using modified waste short optical fibers and specific emulsion systems in cement foamed plates, the hyperbranched structure and hydrophobic layer are formed, which solves the problem of insufficient strength and insulation of cement foamed plates, and achieves high strength, low water absorption and good Composite cement foam board with thermal insulation performance.

CN118834054BActive Publication Date: 2025-02-18NANTONG ZHUYOU ZHIZAO TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411323221.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-02-18
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

Because the cement foamed plate is light and porous, it has high water absorption, resulting in insufficient insulation and strength. The prior art reinforces strength by adding fibers but has poor effect.

Method used

Modified waste short optical fiber and specific emulsion system are used to form a hyperbranched structure through silane coupling agent and photoinitiator, which is uniformly dispersed in the composite cement foam board to form an interpenetrating network and a hydrophobic layer to improve strength and toughness.

Benefits of technology

It significantly improves the strength and toughness of the composite cement foamed plate, reduces the volume water absorption rate, and improves the thermal insulation performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a composite cement foaming board and a preparation method thereof, and relates to the technical field of building materials. The composite cement foaming board comprises the following raw material components: composite cement, fly ash, an early strength agent, a water reducing agent, modified waste short optical fibers, styrene butadiene emulsion, a chain extension monomer emulsion, a foaming agent, 3 to 5 parts by mass of a foam stabilizer, an aqueous photoinitiator and water. The modified waste short optical fibers are obtained by immersing the waste short optical fibers in a silane emulsion, filtering and drying. The chain extension monomer emulsion is obtained by mixing a chain extension monomer, an emulsifier and water. The chain extension monomer adopts a mixture of triallyl phosphate, 1,3,5-triallyl-1,3,5-triazine, 3-(cyclopropylamino)ethyl acrylate, N-(2-aminoethyl)acrylamide, decyl acrylate, 1,9-decadiene and 1,21-docosadiene. The emulsifier adopts emulsifier OP-10.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, in particular to a composite cement foam board and a preparation method thereof. Background Art

[0002] Cement foam board usually refers to a lightweight porous fireproof and thermal insulation material made of cement as the main cementitious material, slag, fly ash, silica fume and other active mineral admixtures, and admixtures such as early strength agent, stabilizer and foaming agent through the process of batching, mixing, pouring, curing, cutting and other processes. It is a product that is further developed from aerated concrete and foamed concrete. Cement foam board has the advantages of high fire resistance, high thermal insulation, light weight, easy bonding, non-toxic and harmless, environmentally friendly and energy-saving, and convenient construction. It has been widely used in the external insulation system of building exterior walls.

[0003] However, it is precisely because the cement foam board is light and porous that it has a high water absorption. The higher the moisture content, the worse the thermal insulation and the lower the strength. In order to improve the strength of the cement foam board, technicians add fibers to enhance the strength of the cement foam board.

[0004] The applicant found that with the rapid development of the optical fiber communication industry, due to the existence and expansion of micro cracks on the optical fiber surface, the erosion of the optical fiber surface by water and water vapor molecules in the atmosphere, and the long-term effect of residual stress when the optical cable is laid unreasonably, the life of the general optical fiber is about 10 to 20 years. The optical fiber replaced every year contains about ten to dozens of tons. The applicant recycled the waste optical fiber and added it to the cement foam board to improve its strength. However, the waste optical fiber is very easy to agglomerate during the addition process, which not only fails to improve the strength of the cement foam board, but also causes the strength of the cement foam board to drop sharply.

[0005] Therefore, the applicant prepared a composite cement foam board to solve the above problems. Summary of the invention

[0006] In order to solve the existing technical problems, the present invention discloses a composite cement foamed board, which comprises the following raw material components by weight: 400-600 parts of composite cement, 100-300 parts of fly ash, 3-10 parts of early strength agent, 3-6 parts of water reducing agent, 18-20 parts of modified waste short optical fiber, 100-150 parts of styrene-butadiene emulsion, 50-100 parts of chain extension monomer emulsion, 7.5 parts of foaming agent, 3-5 parts of foam stabilizer, 2-8 parts of water-based photoinitiator and 250-350 parts of water.

[0007] Furthermore, the composite cement is obtained by mixing ultrafine silicate cement and ultrafine sulphoaluminate cement in a mass ratio of 3 to 5:1.

[0008] Furthermore, the modified waste short optical fibers are obtained by immersing the waste short optical fibers in silane emulsion, filtering and drying.

[0009] Furthermore, the silane emulsion is obtained by mixing (3-epoxypropylpropoxy)trimethoxysilane, polyvinyl alcohol, isobutyltriethoxysilane, a composite emulsification system of Span 80 and OP-10, and water.

[0010] Furthermore, the chain extension monomer emulsion is obtained by mixing a chain extension monomer, an emulsifier, and water; the chain extension monomer is a mixture of triallyl phosphate, 1,3,5-triallyl-1,3,5-triazine, 3-(cyclopropylamino)ethyl acrylate, N-(2-aminoethyl)acrylamide, decyl acrylate, 1,9-decadiene, and 1,21-docosahexadecadiene; and the emulsifier is emulsifier OP-10.

[0011] Furthermore, the foaming agent is hydrogen peroxide.

[0012] Furthermore, the foam stabilizer is a silicone polyether emulsion.

[0013] Furthermore, the water-based photoinitiator is any one of water-based photoinitiator 2959 and water-based photoinitiator TPO-1.

[0014] Furthermore, the water reducing agent is BASF's MELMENT® F10, a melamine-type sulfonated polycondensate powder;

[0015] The present invention also provides a method for preparing a composite cement foam board, comprising the following preparation steps:

[0016] (1) 400-600 parts of composite cement, 100-300 parts by weight of fly ash, 3-10 parts by weight of early strength agent, 3-6 parts by weight of water reducing agent, 3-5 parts by weight of foam stabilizer, and 18-20 parts by weight of modified waste short optical fiber are stirred and mixed at a speed of 100-200 r / min at room temperature for 1-3 minutes to obtain a powder;

[0017] (2) Under light-proof conditions, slowly add a mixture of 100-150 parts by mass of styrene-butadiene emulsion, 50-100 parts by mass of chain extension monomer emulsion, 2-8 parts by mass of aqueous photoinitiator, and 250-350 parts by mass of water at 37°C to the powder, stir and mix at a stirring speed of 400-800 r / min for 1-3 min, then add 7.5 parts by mass of foaming agent, continue stirring for 8-12 seconds, pour into a mold and let it stand for foaming, cure at room temperature for 8-12 hours, and then cure under light radiation for 600 seconds, continue to cure for 12-16 hours, demold, cut, and naturally cure for 28 days to obtain a composite cement foam board.

[0018] Furthermore, the preparation method of the modified waste short optical fiber is as follows: the waste optical fiber is sheared to obtain waste short optical fiber with an average diameter of 125~140μm and a length of 3~6mm; the waste short optical fiber is immersed in a silane emulsion of 50~100 times its mass for 12h, and then filtered and dried to obtain the modified waste short optical fiber; the silane emulsion is obtained by mixing (3-epoxypropylpropoxy)trimethoxysilane, polyvinyl alcohol, isobutyltriethoxysilane, Span 80 and OP-10 composite emulsification system, and water in a volume ratio of 14~16:18~20:12~15:9~11:50~60; the mass ratio of Span 80 and OP-10 in the Span 80 and OP-10 composite emulsification system is 4:1.

[0019] Furthermore, the preparation method of the chain extension monomer emulsion is as follows: under light-proof conditions, 25 to 35 parts by weight of chain extension monomer, 6 to 11 parts by weight of emulsifier, and 5 to 15 parts by weight of water are stirred and mixed at 300 r / min for 1 to 3 minutes to obtain the chain extension monomer emulsion;

[0020] Furthermore, the chain extension monomer is obtained by mixing triallyl phosphate, 1,3,5-triallyl-1,3,5-triazine, 3-(cyclopropylamino)ethyl acrylate, N-(2-aminoethyl)acrylamide, decyl acrylate, 1,9-decadiene, and 1,21-docosahexadecadiene in a mass ratio of 1:1:1.2:1.2:1.2:2~4:3~5.

[0021] Furthermore, the light source is OmniCure S1000UV, and the radiation energy density is 6.5 mW / cm 2 .

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The composite cement foam board prepared by the present invention has high strength, low volume water absorption, good toughness and thermal insulation;

[0024] The invention adopts silane coupling agents (3-epoxypropyl propoxy) trimethoxy silane and isobutyl triethoxy silane to modify waste short optical fibers. The silane functional groups on the surfaces of the waste short optical fibers are hydrolyzed to generate silanol groups, which are dehydrated and condensed with hydroxyl groups on the surfaces of cement particles to form chemical bonds, and are adsorbed on the surfaces of cement particles in a chemically bonded manner, so that the waste short optical fibers are uniformly dispersed in the composite cement foaming board. (3-epoxypropyl propoxy) trimethoxy silane, isobutyl triethoxy silane, PVA and silicone gel form an interpenetrating network inside the composite cement foaming board, and a hydrophobic layer is formed on the pore surface of the composite cement foaming board, thereby improving the strength and water absorption of the composite cement foaming board.

[0025] The invention adds styrene butadiene emulsion and chain extension monomer emulsion, wherein the chain extension monomer of the chain extension monomer emulsion adopts triallyl phosphate, 1,3,5-triallyl-1,3,5-triazine, 3-(cyclopropylamino)ethyl acrylate, N-(2-aminoethyl)acrylamide, decyl acrylate, and flexible long carbon chain 1,9-decadiene and 1,21-docosahexadecadiene, after which the modified waste short optical fiber is rapidly dispersed in the composite cement foaming board to guide the light emitted by the light source, thereby stimulating the inside and outside of the composite cement foaming board. The photoinitiator causes the styrene-butadiene emulsion and chain extension monomer emulsion uniformly dispersed in the composite cement foam board to react under the action of the photoinitiator to form a polymer cross-linked network with a hyperbranched structure containing flexible branches. The amino groups on the polymer cross-linked network react with the epoxy groups on the surface of the modified waste short optical fibers to firmly intersperse the polymer cross-linked network in the composite cement foam board, thereby improving the problem of decreased strength of the composite cement foam board after foaming, increasing the toughness of the composite cement foam board, and ensuring the thermal insulation performance of the composite cement foam board. DETAILED DESCRIPTION

[0026] The present invention is further described in detail below in conjunction with examples, but the following examples should not be construed as limiting the present invention.

[0027] Some of the raw materials of the embodiments of the present invention and the comparative examples are as follows:

[0028] The ultrafine silicate cement and ultrafine sulphoaluminate cement are respectively 42.5 grade ultrafine ordinary silicate cement and 52.5 grade ultrafine sulphoaluminate cement produced by Tangshan Polar Bear Building Materials Co., Ltd.;

[0029] The fly ash is grade I fly ash with a particle size of more than 325 meshes;

[0030] The water used shall be tap water that complies with the provisions of JGJ63-2006 "Standard for Water Used in Concrete Mixing";

[0031] The water reducing agent is BASF's MELMENT® F10, a melamine-type sulfonated polycondensate powder;

[0032] The styrene butadiene emulsion adopts BASF SD623 styrene butadiene emulsion;

[0033] The emulsifier is emulsifier OP-10;

[0034] The photoinitiator is water-based photoinitiator 2959;

[0035] The foam stabilizer is silicone polyether emulsion;

[0036] The early strength agent is the early strength agent XF-2 produced by Hunan Lexian New Material Technology Co., Ltd.

[0037] Example 1

[0038] A method for preparing a composite cement foam board, the preparation steps are as follows:

[0039] (1) 400 parts of composite cement, 100 parts by weight of fly ash, 3 parts by weight of early strength agent, 3 parts by weight of water reducing agent, 3 parts by weight of foam stabilizer, and 18 parts by weight of modified waste short optical fiber were stirred and mixed at a speed of 100 r / min at room temperature for 1 min to obtain a powder;

[0040] (2) Under light-proof conditions, slowly add a mixture of 100 parts by mass of styrene-butadiene emulsion, 50 parts by mass of chain extension monomer emulsion, 2 parts by mass of aqueous photoinitiator, and 250 parts by mass of water at 37°C to the powder, stir and mix at a stirring speed of 400 r / min for 1 min, then add 7.5 parts by mass of foaming agent, continue stirring for 8 seconds, pour into a mold and let it stand for foaming, after curing at room temperature for 8 hours, and then cure under light radiation for 600 seconds, continue curing for 12 hours, demold, cut, and naturally cure for 28 days to obtain a composite cement foam board.

[0041] The preparation method of the modified waste short optical fiber is as follows: the waste optical fiber is sheared to obtain waste short optical fiber with an average diameter of 125 μm and a length of 3 mm; the waste short optical fiber is immersed in a silane emulsion of 50 times its mass for 12 hours, and then filtered and dried to obtain the modified waste short optical fiber; the silane emulsion is obtained by mixing (3-epoxypropylpropoxy)trimethoxysilane, polyvinyl alcohol, isobutyltriethoxysilane, Span 80 and OP-10 composite emulsification system, and water in a volume ratio of 14:18:12:9:50; the mass ratio of Span 80 and OP-10 in the Span 80 and OP-10 composite emulsification system is 4:1.

[0042] The preparation method of the chain extension monomer emulsion is as follows: under light-proof conditions, 25 parts by weight of chain extension monomer, 6 parts by weight of emulsifier, and 5 parts by weight of water are stirred and mixed at 300 r / min for 1 minute to obtain the chain extension monomer emulsion;

[0043] The chain extension monomer is obtained by mixing triallyl phosphate, 1,3,5-triallyl-1,3,5-triazine, 3-(cyclopropylamino)ethyl acrylate, N-(2-aminoethyl)acrylamide, decyl acrylate, 1,9-decadiene, and 1,21-docosahexadecadiene in a mass ratio of 1:1:1.2:1.2:1.2:2:3.

[0044] The light source is OmniCure S1000UV, and the radiation energy density is 6.5mW / cm 2 .

[0045] Example 2

[0046] A method for preparing a composite cement foam board, the preparation steps are as follows:

[0047] (3) 500 parts of composite cement, 200 parts by weight of fly ash, 6 parts by weight of early strength agent, 5 parts by weight of water reducing agent, 4 parts by weight of foam stabilizer, and 19 parts by weight of modified waste short optical fiber were stirred and mixed at a speed of 150 r / min at room temperature for 2 min to obtain a powder;

[0048] (4) Under light-proof conditions, slowly add a mixture of 130 parts by mass of styrene-butadiene emulsion, 80 parts by mass of chain extension monomer emulsion, 5 parts by mass of aqueous photoinitiator, and 300 parts by mass of water at 37°C to the powder, stir and mix at a stirring speed of 600 r / min for 2 min, then add 7.5 parts by mass of foaming agent, continue stirring for 10 seconds, pour into a mold and let it stand for foaming, cure at room temperature for 10 hours, and then cure under light radiation for 600 seconds. Continue to cure for 14 hours, demold, cut, and naturally cure for 28 days to obtain a composite cement foam board.

[0049] The preparation method of the modified waste short optical fiber is as follows: the waste optical fiber is sheared to obtain waste short optical fiber with an average diameter of 135 μm and a length of 5 mm; the waste short optical fiber is immersed in a silane emulsion of 80 times its mass for 12 hours, and then filtered and dried to obtain the modified waste short optical fiber; the silane emulsion is obtained by mixing (3-epoxypropylpropoxy)trimethoxysilane, polyvinyl alcohol, isobutyltriethoxysilane, Span 80 and OP-10 composite emulsification system, and water in a volume ratio of 15:19:13:10:55; the mass ratio of Span 80 and OP-10 in the Span 80 and OP-10 composite emulsification system is 4:1.

[0050] The preparation method of the chain extension monomer emulsion is as follows: 30 parts by weight of the chain extension monomer, 8 parts by weight of the emulsifier, and 10 parts by weight of water are stirred and mixed at 300 r / min for 1 to 3 minutes under light-proof conditions to obtain the chain extension monomer emulsion;

[0051] The chain extension monomer is obtained by mixing triallyl phosphate, 1,3,5-triallyl-1,3,5-triazine, 3-(cyclopropylamino)ethyl acrylate, N-(2-aminoethyl)acrylamide, decyl acrylate, 1,9-decadiene, and 1,21-docosahexadecadiene in a mass ratio of 1:1:1.2:1.2:1.2:3:4.

[0052] The light source is OmniCure S1000UV, and the radiation energy density is 6.5mW / cm 2 .

[0053] Example 3

[0054] A method for preparing a composite cement foam board, the preparation steps are as follows:

[0055] (5) 600 parts of composite cement, 300 parts by weight of fly ash, 10 parts by weight of early strength agent, 6 parts by weight of water reducing agent, 5 parts by weight of foam stabilizer, and 20 parts by weight of modified waste short optical fiber were stirred and mixed at a speed of 200 r / min at room temperature for 3 min to obtain a powder;

[0056] (6) Under light-proof conditions, slowly add a mixture of 150 parts by mass of styrene-butadiene emulsion, 100 parts by mass of chain extension monomer emulsion, 8 parts by mass of aqueous photoinitiator, and 350 parts by mass of water at 37°C to the powder, stir and mix at a stirring speed of 800 r / min for 3 min, then add 7.5 parts by mass of foaming agent, continue stirring for 12 seconds, pour into a mold and let it stand for foaming, cure at room temperature for 12 hours, and then cure under light radiation for 600 seconds, continue to cure for 16 hours, demold, cut, and naturally cure for 28 days to obtain a composite cement foam board.

[0057] The preparation method of the modified waste short optical fiber is as follows: the waste optical fiber is sheared to obtain waste short optical fiber with an average diameter of 140 μm and a length of 6 mm; the waste short optical fiber is immersed in a silane emulsion of 100 times its mass for 12 hours, and then filtered and dried to obtain the modified waste short optical fiber; the silane emulsion is obtained by mixing (3-epoxypropylpropoxy)trimethoxysilane, polyvinyl alcohol, isobutyltriethoxysilane, Span 80 and OP-10 composite emulsification system, and water in a volume ratio of 16:20:15:11:60; the mass ratio of Span 80 and OP-10 in the Span 80 and OP-10 composite emulsification system is 4:1.

[0058] The preparation method of the chain extension monomer emulsion is as follows: 35 parts by mass of the chain extension monomer, 11 parts by mass of the emulsifier, and 15 parts by mass of water are stirred and mixed at 300 r / min for 3 minutes under light-proof conditions to obtain the chain extension monomer emulsion;

[0059] The chain extension monomer is obtained by mixing triallyl phosphate, 1,3,5-triallyl-1,3,5-triazine, 3-(cyclopropylamino)ethyl acrylate, N-(2-aminoethyl)acrylamide, decyl acrylate, 1,9-decadiene, and 1,21-docosahexadecadiene in a mass ratio of 1:1:1.2:1.2:1.2:4:5.

[0060] The light source is OmniCure S1000UV, and the radiation energy density is 6.5mW / cm 2 .

[0061] Comparative Example 1

[0062] The only difference between Comparative Example 1 and Example 2 is that the raw material components include: composite cement, fly ash, early strength agent, water reducing agent, waste short optical fiber, styrene-butadiene emulsion, chain extender monomer emulsion, foaming agent, foam stabilizer, water-based photoinitiator, and water. The remaining steps and ingredients are the same as those in Example 2.

[0063] Comparative Example 2

[0064] The only difference between Comparative Example 2 and Example 2 is that the raw material components include: composite cement, fly ash, early strength agent, water reducing agent, styrene-butadiene emulsion, chain extender monomer emulsion, foaming agent, foam stabilizer, water-based photoinitiator, and water. The remaining steps and ingredients are the same as those in Example 2.

[0065] Comparative Example 3

[0066] The only difference between Comparative Example 3 and Example 2 is that the silane emulsion is obtained by mixing polyvinyl alcohol, isobutyl triethoxysilane, Span 80 and OP-10 composite emulsification system, and water. The remaining steps and ingredients are the same as those in Example 2.

[0067] Comparative Example 4

[0068] The only difference between Comparative Example 4 and Example 2 is that the raw material components include: composite cement, fly ash, early strength agent, water reducing agent, modified waste short optical fiber, styrene-butadiene emulsion, foaming agent, foam stabilizer, water-based photoinitiator, and water; the remaining steps and ingredients are the same as those in Example 2.

[0069] Comparative Example 5

[0070] The only difference between Comparative Example 5 and Example 2 is that the chain extension monomers used are 3-(cyclopropylamino)ethyl acrylate, N-(2-aminoethyl)acrylamide, decyl acrylate, 1,9-decadiene, and 1,21-docosahexadecene, and the remaining steps and ingredients are the same as those in Example 2.

[0071] Comparative Example 6

[0072] The only difference between Comparative Example 6 and Example 2 is that the chain extension monomers used are 3-(cyclopropylamino)ethyl acrylate, N-(2-aminoethyl)acrylamide, and decyl acrylate; the remaining steps and ingredients are the same as those in Example 2.

[0073] Effect example

[0074] Table 1 below shows the performance test analysis results of the composite cement foamed boards prepared by Examples 1 to 3 and Comparative Examples 1 to 6 of the present invention.

[0075] Table 1

[0076]

[0077] It can be found from Table 1 that the composite cement foam board prepared in the embodiment has high compressive strength, low volume water absorption, good flexibility and thermal insulation; Example 2 is compared with Comparative Examples 1 to 3 to find that the composite cement foam board prepared by using the modified waste short optical fiber prepared by silane coupling agent (3-epoxypropylpropoxy)trimethoxysilane has high compressive strength, low volume water absorption, good flexibility and thermal insulation; Example 2 is compared with Comparative Example 4 to find that the composite cement foam board prepared by using chain extension monomer emulsion has high compressive strength, good flexibility and thermal insulation; Example 2 is compared with Comparative Example 5 to find that the composite cement foam board prepared by using triallyl phosphate and 1,3,5-triallyl-1,3,5-triazine has high compressive strength and good thermal insulation; Example 2 is compared with Comparative Example 6 to find that the composite cement foam board prepared by using 1,9-decadiene and 1,21-docosahexadecadiene has good flexibility.

[0078] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

Claims

1. A composite cement foam board, characterized in that: The raw material components include the following by weight: 400-600 parts of composite cement, 100-300 parts of fly ash, 3-10 parts of early strength agent, 3-6 parts of water reducing agent, 18-20 parts of modified waste short optical fiber, 100-150 parts of styrene-butadiene emulsion, 50-100 parts of chain extension monomer emulsion, 7.5 parts of foaming agent, 3-5 parts of foam stabilizer, 2-8 parts of water-based photoinitiator, and 250-350 parts of water; The modified waste short optical fiber is obtained by immersing the waste short optical fiber in a silane emulsion, filtering and drying; the silane emulsion is obtained by mixing (3-epoxypropylpropoxy)trimethoxysilane, polyvinyl alcohol, isobutyltriethoxysilane, Span 80 and OP-10 composite emulsification system and water; the chain extension monomer emulsion is obtained by mixing a chain extension monomer, an emulsifier and water; the chain extension monomer is a mixture of triallyl phosphate, 1,3,5-triallyl-1,3,5-triazine, 3-(cyclopropylamino)ethyl acrylate, N-(2-aminoethyl)acrylamide, decyl acrylate, 1,9-decadiene and 1,21-docosahexadecadiene; the emulsifier is emulsifier OP-10; The silane emulsion is obtained by mixing (3-epoxypropylpropoxy)trimethoxysilane, polyvinyl alcohol, isobutyltriethoxysilane, Span 80 and OP-10 composite emulsification system, and water in a volume ratio of 14-16:18-20:12-15:9-11:50-60; the mass ratio of Span 80 to OP-10 in the Span 80 and OP-10 composite emulsification system is 4:1; The preparation method of the chain extension monomer emulsion is as follows: under light-proof conditions, 25 to 35 parts by mass of a chain extension monomer, 6 to 11 parts by mass of an emulsifier, and 5 to 15 parts by mass of water are stirred and mixed at 300 r / min for 1 to 3 minutes to obtain a chain extension monomer emulsion; the chain extension monomer is obtained by mixing triallyl phosphate, 1,3,5-triallyl-1,3,5-triazine, 3-(cyclopropylamino)ethyl acrylate, N-(2-aminoethyl)acrylamide, decyl acrylate, 1,9-decadiene, and 1,21-docosahexadecadiene in a mass ratio of 1:1:1.2:1.2:1.2:2-4:3-5.

2. The composite cement foam board according to claim 1, characterized in that: The composite cement is obtained by mixing ultrafine silicate cement and ultrafine sulphoaluminate cement in a mass ratio of 3-5:

1.

3. The composite cement foam board according to claim 1, characterized in that: The water-based photoinitiator is any one of water-based photoinitiator 2959 and water-based photoinitiator TPO-1.

4. A method for preparing a composite cement foam board according to any one of claims 1 to 3, characterized in that: The method comprises the following preparation steps: (1) 400-600 parts of composite cement, 100-300 parts by weight of fly ash, 3-10 parts by weight of early strength agent, 3-6 parts by weight of water reducing agent, 3-5 parts by weight of foam stabilizer, and 18-20 parts by weight of modified waste short optical fiber are stirred and mixed at a speed of 100-200 r / min at room temperature for 1-3 minutes to obtain a powder; (2) Under light-proof conditions, slowly add a mixture of 100-150 parts by mass of styrene-butadiene emulsion, 50-100 parts by mass of chain extension monomer emulsion, 2-8 parts by mass of aqueous photoinitiator, and 250-350 parts by mass of water at 37°C to the powder, stir and mix at a stirring speed of 400-800 r / min for 1-3 min, then add 7.5 parts by mass of foaming agent, continue stirring for 8-12 seconds, pour into a mold and let it stand for foaming, cure at room temperature for 8-12 hours, and then cure under light radiation for 600 seconds, continue to cure for 12-16 hours, demold, cut, and naturally cure for 28 days to obtain a composite cement foam board.

5. The method for preparing the composite cement foam board according to claim 4, characterized in that: The preparation method of the modified waste short optical fiber is as follows: the waste optical fiber is sheared to obtain waste short optical fiber with an average diameter of 125-140 μm and a length of 3-6 mm; the waste short optical fiber is immersed in a silane emulsion with a mass of 50-100 times that of the waste short optical fiber for 12 hours, and then filtered and dried to obtain the modified waste short optical fiber.

6. The method for preparing the composite cement foam board according to claim 4, characterized in that: The light source is OmniCure S1000UV, and the radiation energy density is 6.5mW / cm 2 .

Citation Information

Patent Citations

  • Fiber reinforced thermal insulation concrete wall body

    CN108558296A

  • Aramid fiber modified polymer cement waterproof coating and preparation method thereof

    CN113861765A